Physiological Age Status of Female Adults and Off-Season Survival of Rice Leaffolder Cnaphalocrocis medinalis in India - Padmavathi Chintalapati; Katti Gururaj; Sailaja Vallabuni; Prasad Yenumulag (Rice Science, 2015)
Rice leaffolder, Cnaphalocrocis medinalis, is one of the major foliage feeders found in the rice growing regions in India. When the crop was at maturity, numerous adults of rice leaffolder were found in the rice fields though the larval population gradually decreased, and no eggs were found on rice leaves. The population characteristics of C. medinalis were assessed based on the physiological age status of adults at different crop growth stages. Based on egg development within ovarioles, ovariole appearance, number and colour of fat bodies, and characteristics of bursa copulatrix, physiological age status of the adults was described, which served as a basis for the determination of age composition. C. medinalis adults were found during the first week of August on rice plants, of which 44% were in Age 0 with immature ovaries, indicating immigrants. However, 28% adults each were at Ages 1–2 with developing ovaries, indicating local breeding population. The carryover and off-season survival of C. medinalis were also studied to determine the contribution of the alternative hosts in the population growth that helped in devising efficient management strategies. Rice was the most preferred host followed by Triticum aestivum, Echinochloa crusgulli and Brachiaria plantaginea. Various routes of the carryover of C. medinalis from season to season were discussed.